Circular Arc Crack And Concentric Inhomogeneity in an Infinite Isotropic Elastic Plate Under Tension - Bhargava, R.R; Narayan, Ram (Engineering Transactions, 1975)
A circular inhomogeneity is embedded in an infinite elastic material which also contains a circular arc crack. The inhomogencity and the crack are concentric but the radius of the crack is greater than that of inhomogeneity. The infinite plate is subject to a traction at infinity. The above elasticity problem is solved in this paper using complex variable method, in the circular region bounded by the radius of the crack including inhomogeneity. Some numerical calculations have been done. It is seen that a more flexible inhomogeneity than outside material decreases the stress intensity factor at the tips of the crack. Also, as expected, the stress intensity factor increases as the crack moves away from the inhomogeneity in the case when the inhomogeneity is more flexible than outside material, while it decreases in the case of more rigid inhomogencity.